AB1036 Ultrasound in Carpal Tunnel Syndrome: Predictive Value of Baseline B-Mode and Power Doppler Assessment for Long-Term Functional Outcome. (9th June 2015) - Marschall, A.; Ficjian, A.; Husic, R.; Stradner, M.; Zauner, D.; Seel, W.; Simmet, N.E.; Klammer, A.; Heizer, P.; Brickmann, K.; Gertler, J.; Fürst-Moazedi, F.C.; et al.
Abstract : Background: The diagnostic value of ultrasound imaging in Carpal Tunnel Syndrome (CTS) by means of measurement of the Cross-sectional Area (CSA) of the median nerve has been established. However, reports on its prognostic value regarding the long term outcome is rare and contradictory. Objectives: To investigate the prognostic value of baseline B-mode and Power Doppler (PD) ultrasound assessment of the median nerve in CTS patients regarding their long-term functional outcome. Methods: Out of 36 patients with suspected CTS we conducted a prospective study on 27 patients with confirmed CTS, who underwent baseline visit and two follow-up visits: short-term after 2, 8 months, long-term after 26, 8 months (mean). Clinical, neurophysiological (NCS) and sonographic evaluation was performed at each visit. Ultrasound was performed using a Logiq E9 ultrasound device with multifrequence linear transducer, measuring the CSA of the median nerve at the following anatomic levels: (1) proximal border of the Pronator quadratus muscle (CsP), (2) area of the proximal Third of the pronator quadratus muscle (CsT) and (3) in the carpal canal, level of the Scaphoid tubercle and pisiform bone (CsS). PD-signals were graded from 0-3. Clinical outcome was evaluated regarding patients clinical improvement, based on: (1) the DASH questionnaire, (2) the visual analogue scale for grading pain symptoms (painVAS), (3) the VAS for grading severity of the clinical condition, completed by the examiner (physVAS). We conducted multivariate inclusive logistic regression models (including age, gender, BMI, vascularisation and symptom duration as independent variables) to determine the predictive value of CSA and PD for the binary dependent variable of outcome: improvement/no improvement of both at least 20% and 70%. Results: 42, 2% and 33, 3% of the CTS patients showed improvement regarding painVAS, 53, 3% and 42, 2% presented improvement of their physVAS and 37, 8% and 15, 6% showed improvement of DASH outcome measure of at least 20% and 70% from baseline to long-term follow-up, respectively. CsS, CsS/CsP and CsS/CsT were higher in patients without improvement compared to those with at least 20% or 70% improvement. CsS/CsP presented the most relevant predictive value for clinical improvement, being significant in all logistic regression models predicting an improvement of at least 20% (exp(B): 0, 000 – 0, 012, p<0, 05). In models predicting an improvement of at least 70%, CsS/CsP showed to be significant for painVAS and almost reached significance for physVAS and DASH (p=0, 069 and p=0, 076 respectively). We found similar results for CsS/CsT (being significant in all regression models predicting an improvement of at least 20%) and CsS (being significant in models predicting an improvement of at least 20% of painVAS and DASH and predicting an improvement of at least 70% of painVAS). Since surgery can not be considered to be an independent variable, models including this factor resulted to be insignificant. Conclusions: A higher CsA at baseline predicts a worse clinical outcome of CTS patients as determined by VAS and DASH. PD examination has no predictive value regarding CTS outcome. Disclosure of Interest: None declared